1997
DOI: 10.1029/97gl01999
|View full text |Cite
|
Sign up to set email alerts
|

Mesospheric standing waves near South Pole

Abstract: Abstract. Optical measurements of mesospheric winds near South Pole, during August 1996, show the presence of large-scale standing waves with periods of 51.3-hr and 107-hr, respectively. In addition, a 11.6-hr period zonal wavenumber-one oscillation with a westward phase progression was also observed. The direction of the observed mean wind has changed nearly 60 ø westward from the typical wind direction observed during the same month in previous years. The direction of the presently observed mean wind is near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 14 publications
4
27
1
Order By: Relevance
“…The amplitude variation is systematic and can be described by a sinusoidal variation. A similar Hernandez et al (1997) which they attributed to a mesospheric standing oscillation. It appears that event 7 is consistent with the structure that Hernandez et al (1997) observed and may be considered a mesospheric standing oscillation.…”
Section: Identi®cation Of Wave Eventsmentioning
confidence: 71%
See 2 more Smart Citations
“…The amplitude variation is systematic and can be described by a sinusoidal variation. A similar Hernandez et al (1997) which they attributed to a mesospheric standing oscillation. It appears that event 7 is consistent with the structure that Hernandez et al (1997) observed and may be considered a mesospheric standing oscillation.…”
Section: Identi®cation Of Wave Eventsmentioning
confidence: 71%
“…A similar Hernandez et al (1997) which they attributed to a mesospheric standing oscillation. It appears that event 7 is consistent with the structure that Hernandez et al (1997) observed and may be considered a mesospheric standing oscillation. Event 7 has a period close to 5.2 days (124 h), an amplitude of 8.9 AE 0.2 m s À1 and is propagating along the 121 E± 301 E AE 1.2 meridian.…”
Section: Identi®cation Of Wave Eventsmentioning
confidence: 71%
See 1 more Smart Citation
“…It can be easily seen that the selected oscillations reveal a very de®nite transient nature and are mainly separated by their time of appearance. Such transient behavior for the wind oscillations over the South Pole with periods of 11.6 h and 10 h has been noticed earlier (Hernandez et al, 1995;Hernandez et al, 1997). Usually each oscillation is signi®cant only for several periods of its existence.…”
Section: Frommentioning
confidence: 90%
“…They include di erences in the sampling statistics for di erent directions; frequency spectrum and background noise levels for di erent directions. In addition there are some background oscillations, perhaps as observed by Hernandez et al (1997) and Palo et al (1998), which may modulate the waves considered mainly in one direction and distort the spectrum.…”
Section: Frommentioning
confidence: 99%